A giant parathyroid adenoma mimicking a thyroid swelling: A case report (Indian Journal of Case Reports, 2024)
Giant parathyroid adenomas are uncommon. Its clinical management is challenging. Our study’s goal is to share our experience with pre-operative localization of parathyroid adenomas while emphasizing the importance of intraoperative parathyroid hormone (IOPTH) assays in such situations. Here, we present the case of a 46-year-old woman who was diagnosed with parathyroid adenoma. The clinical aspects, pre-operative management, and surgical procedure have all been examined. Parathyroid hormone levels were reduced by 90% following surgical removal of the tumor and an IOPTH assay. IOPTH significantly improves surgical success rates in patients with only one positive imaging test result and adds significant value to surgical decision-making.